2014
DOI: 10.1002/2013jc009301
|View full text |Cite
|
Sign up to set email alerts
|

The great 2012 Arctic Ocean summer cyclone enhanced biological productivity on the shelves

Abstract: [1] A coupled biophysical model is used to examine the impact of the great Arctic cyclone of early August 2012 on the marine planktonic ecosystem in the Pacific sector of the Arctic Ocean (PSA). Model results indicate that the cyclone influences the marine planktonic ecosystem by enhancing productivity on the shelves of the Chukchi, East Siberian, and Laptev seas during the storm. Although the cyclone's passage in the PSA lasted only a few days, the simulated biological effects on the shelves last 1 month or l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 58 publications
0
32
0
Order By: Relevance
“…BIOMAS is a coupled biophysical model (Zhang et al, 2010a(Zhang et al, , 2014) that has three model elements: a sea ice model, an ocean circulation model, and a pelagic biological model. The pelagic biological model is an 11-component marine pelagic ecosystem model that includes two phytoplankton components (diatoms and flagellates), three zooplankton components (microzooplankton, copepods, and predator zooplankton), dissolved organic nitrogen, detrital particulate organic nitrogen, particulate organic silica, nitrate, ammonium, and silicate (see Fig.…”
Section: Model Elementsmentioning
confidence: 99%
See 3 more Smart Citations
“…BIOMAS is a coupled biophysical model (Zhang et al, 2010a(Zhang et al, , 2014) that has three model elements: a sea ice model, an ocean circulation model, and a pelagic biological model. The pelagic biological model is an 11-component marine pelagic ecosystem model that includes two phytoplankton components (diatoms and flagellates), three zooplankton components (microzooplankton, copepods, and predator zooplankton), dissolved organic nitrogen, detrital particulate organic nitrogen, particulate organic silica, nitrate, ammonium, and silicate (see Fig.…”
Section: Model Elementsmentioning
confidence: 99%
“…The pelagic biological model is an 11-component marine pelagic ecosystem model that includes two phytoplankton components (diatoms and flagellates), three zooplankton components (microzooplankton, copepods, and predator zooplankton), dissolved organic nitrogen, detrital particulate organic nitrogen, particulate organic silica, nitrate, ammonium, and silicate (see Fig. 3 in Zhang et al, 2014; also see Kishi et al, 2007). Values of key biological parameters used in the model are listed in Zhang et al (2010a).…”
Section: Model Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous modeling analysis indicated that plankton productivity over the Chukchi, East Siberian, and Laptev shelves was enhanced by vertical mixing with nutrient replenishment and lateral plankton transport from the western Arctic basin during the cyclone storm (Zhang et al, 2014). It is assumed that synoptic cyclone activities have both positive and negative contributions to ice algal production.…”
Section: Impact Of Great Cyclone Activitymentioning
confidence: 99%